Controlling Delivery Of Capsaicin From Layered-Flat Noodles Using Gastro-Resistant Dough Layers - Li, Ling Yun (2013)
This thesis describes the development of a novel capsaicin controlled-release/delivery using redesigned yellow alkaline noodles (i.e. layered noodles, LN) as the delivery system. The proposed LN was prepared by sandwiching the capsaicin-enriched dough (CED) in between two gastro-resistant layers. In the preliminary study, the formulation of CED was designed and the feasibility of using LN as a capsaicin-carrier was explored. In comparison with conventional noodles (CN) with equal amount of capsaicin, LN was proven to have significantly lower (P < 0.05) capsaicin losses during cooking and shorter lingering period of spiciness in the mouth after consuming the noodles. To withstand the gastro-intestinal conditions, application of gastro-resistant layers to produce LN was examined. The gastro-resistant layers were made from (a) wheat flour (LN-C), (b) wheat flour mixed with resistant starch flour (Fibersym®) (LN-F) and (c) wheat flour mixed with soy protein isolate (SPI) and microbial transglutaminase (MTG) (LN-MTG), respectively. Physicochemical properties, texture properties, capsaicin retentions and predicted glycemic index (pGI) of the developed LN were examined. LN-MTG showed the highest (P < 0.05) tensile strength and elasticity, as well as the highest (P < 0.05) capsaicin retention in stimulated mouth and intestinal conditions. In stimulated gastric conditions, the capsaicin retention of all noodles was similar. The pGI of LN-MTG and LN-F were similar (P > 0.05) and were significantly lower (P < 0.05) than LN-C.